Roman art - Strong, Donald Emrys; Ling, Roger; Toynbee, J. M. C., (Jocelyn M. C.), d. 1985. (New Haven [Conn.] : Yale University Press, 1995)
Traces the development of Roman art from the early Iron Age to the end of the fourth century A.D., examining artifacts from tenth and ninth century B.C. graves to the paintings and mosaics from Constantine the Great.
Includes bibliographical references (p. [375]-387) and index.
Adult
Keywords: Art, Roman; Roman art